Great battlefields of the world - Macdonald, John 1945- (Chartwell Books, 1987)
A stunning new look at 30 of the most significant battles in world history, this book includes fully illustrated and vividly told accounts of fascinating battles from ancient to modern times. 3-dimensional graphics reveal troop plans and detailed features including weapons innovations reveal how many battles were won and lost.